ON THE PROBLEM OF TYPOLOGY OF ASYNDETICAL CONSTRUCTIONS IN RUSSIAN AND FRENCH (Proceedings of Southern Federal University. Philology, 2013)
Dudnikova L.V.Keywords: asyndetical composite sentence, asyndeton, juxtaposition, structure, semantics, text.The article is devoted to the description of the asyndetical composite sentence as a unit of syntax. The existing approaches to the interpretation of asyndetical constructions in Russian and foreign linguistics are under analysis. The problem of status and typology of these constructions, their relation to the text and to the composite sentence, such as the complex and the compound sentence, are studied. А special attention is given to the analysis of their structural and semantic features in the Russian and French languages. The article describes the oppositions of the uniform and not uniform composition, the oppositions of the open and closed structures and others.